The The Significance of Internal and External Relativism For Religious Harmony - Zaprulkhan Zaprulkhan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
Abstract In the public sphere, internal relations between fellow Muslims appear negative. Some Muslims insult, curse and slander each other. Likewise, relations between religious communities externally show a less harmonious relationship. There is mutual suspicion in the relationship between religious communities externally. Some Muslim scholars offer the concept of internal relativism as a solution for relations between fellow Muslims internally and the concept of external relativism as a solution for relations between various religious communities in the public space. Therefore, this article tries to elaborate on the significance of the construction of internal and external relativism in building ukhuwah Islamiyah internally and harmony among religious communities externally. Keywords: significance, internal and external relativism, religious harmony Abstrak: Dalam ruang publik, relasi internal antara sesama umat Islam tampak negatif. Sebagian umat Islam saling mencaci menjelekkan satu sama lain, saling mengutuk dan memfitnah. Begitu pula, relasi antara umat beragama secara eksternal memperlihatkan hubungan yang kurang harmonis. Ada sikap saling curiga dalam hubungan antara umat beragama secara eksternal. Sebagian cendikiawan muslim menawarkan konsep relativisme internal sebagai solusi bagi relasi antara sesama umat Islam secara internal dan konsep relativisme eksternal sebagai solusi bagi relasi antara berbagai umat beragama di ruang publik. Karena itu, artikel ini mencoba untuk menguraikan signifikansi konstruksi relativisme internal dan eksternal dalam membangun ukhuwah islamiyah secara internal dan kerukunan antar umat beragama secara eksternal. Kata kunci: signifikansi, relativisme internal dan eksternal, harmoni agama